2012
DOI: 10.1016/j.ajo.2012.03.048
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Consumption of Fruits/Vegetables With Decreased Risk of Glaucoma Among Older African-American Women in the Study of Osteoporotic Fractures

Abstract: Purpose To explore the association between consumption of fruits and vegetables and the presence of glaucoma in older African American women. Design Cross-sectional study. Methods Disc photographs and suprathreshold visual fields were obtained from the 662 African American participants in the Study of Osteoporotic Fractures. Masked, trained readers graded all discs, and two glaucoma specialists reviewed photos and visual fields. The Block Food Frequency Questionnaire assessed food consumption. Relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 39 publications
4
81
0
1
Order By: Relevance
“…Also, as both cohorts are 90+% Caucasian, our results may not be generalizable; however, in a study of African-Americans, kale/collard intake was also associated with a lower POAG risk. 46 Finally, these data represent findings from the first population-based observational study, and thus, the association between dietary nitrate consumption and POAG should be interpreted cautiously and confirmed.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Also, as both cohorts are 90+% Caucasian, our results may not be generalizable; however, in a study of African-Americans, kale/collard intake was also associated with a lower POAG risk. 46 Finally, these data represent findings from the first population-based observational study, and thus, the association between dietary nitrate consumption and POAG should be interpreted cautiously and confirmed.…”
Section: Discussionsupporting
confidence: 52%
“…74-79 Therefore, dietary nitrate supplementation represents a practical method to increase NO levels. Indeed, across the two cross-sectional studies in all (95 cases among 1,155 total) 45 or only African-American (77 cases among 587 total) 46 women in the Study of Osteoporotic Fractures, the only vegetable that was consistently inversely associated with POAG was kale/collard greens: ≥ 1 serving/month of kale/collard greens was significantly associated with 55-70% reduced odds of POAG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that a higher intake of certain fruits and vegetables rich in vitamin A, C, B 2 and carotenoids by 1155 older white women was associated with a decreased risk of glaucoma among them [29]. It also been reported that higher intake of vitamin A and C and carotenoids may be associated with decreased likelihood of glaucoma among 662 older African-American women [30].There has been no compelling evidence to suggest a relationship between dietary supplementation with vitamins A or E and glaucomatous disease in the large population-based study. There was, however, weak evidence that supplemental vitamin C intake may perhaps be associated with decreased odds of glaucoma [31].…”
Section: Antioxidants Intakementioning
confidence: 91%
“…Some observational studies investigated the association between "vitamin A" or retinol intake and eye health-related outcomes, including cataract (one cross-sectional study (Cumming et al, 2000); one prospective study (Chasan-Taber et al, 1999)), age-related maculopathy (one cross-sectional study (Smith et al, 1999)) and age-related macular degeneration (one case-control study (Seddon et al, 1994)) and glaucoma (one cross-sectional study (Giaconi et al, 2012); two cohort studies (Kang et al, 2003;Ramdas et al, 2012)). Results were limited and/or inconsistent.…”
Section: Vitamin a Intake And Health Consequencesmentioning
confidence: 99%